PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN (Studi Pada Politeknik Tanah Laut Di Kabupaten Tanah Laut) - Hasan Ismail; Rini Rahmawati (Universitas Lambung Mangkurat, 2014)
Leadership style and work motivation are elements that can affect on job satisfaction to improve employees’ job satisfaction. This research aims to know and analyze the influence of leadership style and work motivation on employees’ job satisfaction on the Polytechnic Tanah laut in Tanah Laut Regency. The type of research is explanatory research. All of the population are the samples of the research. Extracting information on 81 employees’ who were the respondents in the study, by using questionnaire in five scales of likert. Data analysis is taken from multiple linear regression analysis, Coefficient of Multiple Determination, F-test and t-test. The results showed leadership style and work motivation partially or simultaneously positive and significant effect on the the employees’ job satisfaction. Based on these results, implications for the management employees’ that further enhance the confidence of the leadership and employees’ motivation in order to improve employees’ job satisfaction and institutional goals can be achieved.